Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1155/2016/8703239
|View full text |Cite
|
Sign up to set email alerts
|

Cortex phellodendri Extract Relaxes Airway Smooth Muscle

Abstract: Cortex phellodendri is used to reduce fever and remove dampness and toxin. Berberine is an active ingredient of C. phellodendri. Berberine from Argemone ochroleuca can relax airway smooth muscle (ASM); however, whether the nonberberine component of C. phellodendri has similar relaxant action was unclear. An n-butyl alcohol extract of C. phellodendri (NBAECP, nonberberine component) was prepared, which completely inhibits high K+- and acetylcholine- (ACH-) induced precontraction of airway smooth muscle in trach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…According to the dose-contraction curve (see supplementary material, Fig. S1B) and the results of our previous studies [39, 44], the effective concentration 100% (EC 100 ) was 80 mM, which could maximally activate Ca 2+ permeable channels; thus, this concentration was applied. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the dose-contraction curve (see supplementary material, Fig. S1B) and the results of our previous studies [39, 44], the effective concentration 100% (EC 100 ) was 80 mM, which could maximally activate Ca 2+ permeable channels; thus, this concentration was applied. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further identify the NSCCs involved in TSU-68-blocked Ca 2+ influx at the molecular level, the TRPC3 inhibitor Pyr3 [44, 53] and gadolinium, which is a blocker of TRPC1, 3, 5, 6, and 7 [54], were applied sequentially. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, ASM contraction was indirectly measured in mouse lung slices 25 , 27 . Briefly, after the mice were euthanized, the tracheae and lungs were exposed.…”
Section: Methodsmentioning
confidence: 99%
“…To further identify the specific components of NSCCs involved in coptisine-blocked Ca 2+ influx, TRPC3 inhibitor Pyr3 [29,30] and gadolinium, which is a blocker of TRPC1, 3, 5, 6 and 7 [31] were employed sequentially. As shown in Figure 6E,F, in the presence of nifedipine, ACh induced a transient contraction under Ca 2+ -free conditions, which indicated that intracellular Ca 2+ was transiently released after the addition of ACh.…”
Section: Coptisine Blocked Ach-evoked Ca 2+ Influxmentioning
confidence: 99%